Applications of xylans and lignins extracted from lignocellulosic materials for obtaining bioproducts - Barbosa, Bianca Moreira (2017)
The search for better use of wood in the pulp and lignocellulosic biomass industry, such as the fibers of industrial processing corn, has fueled the interest in a more rational use of its components, particularly xylans and lignin. In this context, the objectives of this thesis, consisting of four chapters, were the application of xylans extracted from lignocellulosic materials and the use of Kraft lignin as a pellet additive. Initially, the impact of xylan removal and xylan redeposition on the properties of pulp for tissue paper and printing and writing paper (P&W). Removal of xylans decreased pulp beatability, water retention value and tensile index, but increased water absorption capacity, Klemm capillarity and bulk, presenting almost ideal properties for tissue paper grade pulps. In a second step of the research, cold caustic extraction (CCE) extracted xylans from bleached (BXL) and bleached (WXL) eucalyptus pulps (WXL) were added to a commercial brown pulp in the oxygen delignification (O-stage) step and then bleached. The bleachability of the pulp was not impaired by the deposition of WXL xylan, but slightly negatively affected by BXL xylans. Pulp beatability and the physical and mechanical properties were improved by deposition of xylan. Extraction of xylans by CCE with subsequent deposition in the pulp at the O-stage stage proved attractive for manufacturing high xylan P&W paper grades. Xylans extracted from corn fibers (16.9% xylans) by CCE were added to commercial brown pulp (eucalyptus and pinus) at O- stage and subsequently bleached. The deposition of hemicelluloses occurred in a variable degree (up to 7% in pulp weight). The bleachability of the pulp was not impaired by the deposition of xylans for eucalyptus and pinus. The deposition of hemicellulose in the fibers was more efficient in the eucalyptus pulp than in the pinus. Extraction of xylan from corn fibers by CCE with subsequent deposition in the pulp at O-stage increases the pulp beatability and quality for P&W paper grades. The chemical characterization of corn fibers, the isolation of hemicelluloses using NMR and FTIR- ATR was performed, in addition to a structural investigation of lignins, acid-soluble lignin (ASL) and acid insoluble lignin (AIL), formed by the Klason method by pyrolysis-gas chromatography/mass spectrometry (Py-GC-MS). Hemicellulose isolation can be considered efficient and more 45 primary pyrolysis products for ASL and 39 for AIL from corn fibers. Analytical pyrolysis of ASL from corn fibers showed prevalence of peaks related to products derived from extractive and proteins. Also, the Py-GC-MS technique allowed identifying the presence of derivatives lignin in ASL and AIL. The evaluation of the quality of the pellets produced from a mixture of eucalyptus and corn residue, with the addition of different percentages of Kraft lignin was carried out. For the production of pellets, wood with bark of a hybrid of Eucalyptus grandis x Eucalyptus urophylla and corn residue were used as raw material. The following proportions of corn residue in the mixture were 0, 20, 25 and 30% (w/w). Except for the control (0% w/w lignin), 2 and 5% (w/w) Kraft lignin were added to the raw material in the 4 different mixtures. Pellets were produced in a laboratory press pelletizer with horizontal circular array. The addition of Kraft lignin to eucalyptus and corn residue pellets improved bulk density, and mechanical durability. The mixing of eucalyptus with corn residue is an effective way to optimize properties of biomass solid fuel. Thus, similar amounts to that of the treatment with the proportion of 80% (w/w) eucalyptus and 20% (w/w) corn residue can be a viable alternative to the production of pellets.